(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Sinapic acid (SA) is a potent nutraceutical or natural bioactive compound which is commonly present in the human diet. It was evaluated for its anti-inflammatory activity by in- vitro methods like albumin denaturation assay, heat induced and hypotonicity induced haemolysis, Cycloxygenase-2 (COX-2) and lipoxygenase (5-LOX) inhibition assay at different concentrations. Aspirin (200 μg/ml) and Indomethacin (100 μg/ml) were used as standard drugs. The results showed that Sinapic acid at a concentration range of 10-500 μg/ml significantly (P<0.001) protected the heat induced protein denaturation. Heat and hypotonicity induced haemolysis of erythrocyte was significantly (P<0.001) inhibited at the concentration of 500 μg/ml. The (COX-2) and (5-LOX) enzymes were significantly (P<0.001) inhibited by Sinapic acid. The results indicate that Sinapic acid may be a potential anti-inflammatory agent.